Enhancing Building Depreciation Models Integrating Obsolescence Factors in Modern Built Heritage (Global Journal of Human-Social Science, 2024)
This article is part of a master's thesis that aims to present an adaptation to the Ross-Heidecke model for calculating building depreciation. In addition to including the obsolescence coefficient, the adaptation of the conservation coefficient is proposed based on parameterization from the Dutch standard for building inspection. The proposed method is applied in hypothetical cases where levels of conservation, obsolescence, and useful life can be evaluated under extreme situations. The inclusion of the obsolescence coefficient for determining building depreciation is essential, as it assists in developing a more accurate assessment, resulting in a reduction of subjectivity. To verify the applicability of the method, hypothetical situations were established as a way of evaluating the behavior of depreciation in extreme situations, verifying results trend and whether the method applies to different cases. it can be stated that the applicability of the method presents results within the logical criteria already established by Ross-Heidecke, in addition to demonstrating the influence of obsolescence on the calculation of depreciation.
Keywords: obsolescence; depreciation; ross-heidecke; heritage